Kualitas Semen Segar Kuda (Equus caballus) di Kabupaten Deli Serdang - Sari, I. P.; Hanafi, N. D.; Hamdan, Hamdan; Hasan, F. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
The fresh semen evaluation is very important for stallion before doing artificial insemination. This study aims to determine the quality of semen of the stallion in Deli Serdang regency and semen test at the Regional Artificial Insemination Center, North Sumatera in August-September 2017. This study was conducted on 10 male stallions aged 2-4 years in the district. then the data in show in the form of descriptive. The results showed that in macroscopic test the color of cement is white gray, consistency is watery, pH equal to 6,7 ± 0,48. In motility microscopic test (M%) of 69 ± 0.1, concentrations of 134.5 ± 0.94 x 107 / ml, and sperm condition 80% normal. Based on motility (M%) and concentration of semen quality with progressive spermatozoa movement and concentration of 134.5 million / ml of good horse to be superior male.